FORTUNE - TURTLE: THE SUPPORTING GUIDELINE FOR FOLK WISDOM OF FORTUNE - TURTLE PROCESSING, CASE STUDY : COMMUNITY ENTERPRISE GROUP OF TOOKTA VILLAGE AT MOO 7,HUASAI, HUASAI, NAKORN SI THAMMARAT. - ภูมิสุวรรณ รัตน์นก; เดโชชัย อุดมศักดิ์; ดำรงวัฒนะ จิตติมา; แขน้ำแก้ว เดโช (Journal of MCU Nakhondhat, 2015)
The objective of this research were as follow : 1. to study the folk wisdom of Fortune-turtle processing, and 2. to study the supporting guideline for folk wisdom of Fortune-turtle processing, Case study : Community Enterprise Group of Tookta village at Moo 7, Huasai, Huasai, Nakorn Si Thammarat. This research was qualitative research. The research results found that: the folk wisdom of Fortune-turtle processing had overview totally as follow ; 1) they used objects for processing that had A2 quality level, 2) they chosen the objects and equipment which were in community ,3) they create and develop the pattern always 4) they had agency for raising level of produced processing and sell. the supporting guideline for folk wisdom of Fortune-turtle processing as follow ; 1) conservation this folk wisdom : they would applied to trend to keep at old identity, 2) professional group development : they had founder who had knowledge and expert 3) Instruction knowledge : they must transfer for generation to generation into their family only and promoted knowledge by raising level of Fortune-turtle processing to be original of learning for students and people. Summary of this research was Fortune-turtle processing that could be original of supporting career for people in local until they could develop to make learning processing and apply to use it in their life quite.